Pengembangan Budidaya Ikan Kuwe di Kecamatan Mawasangka Tengah Kabupaten Buton Tengah - Arni Fauziah Rante; Sukri Nyompa; Ichsan Invanni (UNM Geographic Journal, 2020)
This study aims to determine: 1) Knowing what factors support kuwe fish cultivation, 2) Knowing the obstacles faced in the kuwe fish cultivation business and what efforts are being made to deal with these obstacles. 3) Knowing the prospect of developing kuwe fish farming. The location of the research was carried out in Mawasangka Tengah District, Central Buton Regency. The population of this research is all the kuwe fish farming farmers. The targets in this study were 9 kuwe fish farmers. Data was collected using observation, interview, and documentation techniques. The data were analyzed descriptively quantitatively. The results of this study indicate that: 1) The supporting factors in the Kuwe fish farming business are the availability of assistance from the government in the form of Quadrilateral Floating Cages (KJA) / Flexi Type Box. 2) In the processing of kuwe fish cultivation in Mawasangka Tengah District, there are also obstacles faced by kuwe fish farmers, namely lack of capital, large waves and disease. 3) that the Kuwe fish farming business is prospective to be developed. In addition, after a feasibility test using the formula was found, evidence was also found that the kuwe fish farming business was a viable business so that it could be developed in order to be able to improve the economy of the people of Central Mawasangka District.